2021
DOI: 10.3389/fpsyt.2021.659245
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits in Burning Mouth Syndrome Patients With and Without a History of Depression

Abstract: Objectives: So far, the strong link between neuroticism, chronic pain, and depression has been well-documented in literatures. Some suggested that they might share etiological factors, thus resulting in overlapping constructs. However, such effect has never been tested in burning mouth syndrome (BMS) patients, a complex phenomenon influenced by both neuropathic and psychopathological factors. We aim to clarify how personality affects individual's pain and pain-related experiences.Methods: Two hundred forty-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Burning in the mouth is a symptom that arises as a result of complex dynamics, from hysterical conversion to inability to realize separation (divorce, loss of relationships, children becoming adults) and the error of "failure" in the narcissistic core (sense of identity, "What's mine", "who am I?") [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burning in the mouth is a symptom that arises as a result of complex dynamics, from hysterical conversion to inability to realize separation (divorce, loss of relationships, children becoming adults) and the error of "failure" in the narcissistic core (sense of identity, "What's mine", "who am I?") [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients have mental disorders or a history of psychiatric treatment prior to the onset of the syndrome • Manifests itself in older women (65+) due to specific biological and/or psychological factors • 79% of patients have alexithymia (according to the examination using the TAS-20 scale,difficulties in identifying and describing feelings) [4] • Violation of the regulation of negative affect • Violation of symbolic thinking, limited fantasy life • Externally oriented cognitive style • Difficulties in distinguishing feelings from bodily sensations, as well as violations of intuition and empathy.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, various questionnaires have been used in the assessment of pain in patients with BMS in order to evaluate every feature of this multidimensional symptomatology. 3 Traditionally, the Visual Analogue Scale (VAS), 5,6 the Numeric Rating Scale (NRS) 7 and the short form of the McGill Pain Q uestionnaire (SF-MPQ ) [8][9][10] have been the most frequently used tools for measuring and estimating pain intensity and quality in BMS. In addition, recently, in three studies [11][12][13] the Pain DETECT Questionnaire (PD-Q) has been used in a screening stage to evaluate the neuropathic component of pain in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among personality traits, research has particularly investigated neuroticism with components of introversion and hostility 10 11. A recent study has shown that neuroticism correlates with a more serious condition for BMS patients with and without a psychiatric history of depression 12. Alexithymia, a psychological trait elevated in individuals with chronic pain,13 should be routinely screened in those patients 14 15.…”
Section: Introductionmentioning
confidence: 99%